Distinctive toxic repercussions of polystyrene nano plastic towards aquatic non target species Nitrobacter vulgaris, Scenedesmus sp and Daphnia magna - Nagaraja, Sowmya Sri; Gouda, Yerimma; Miguez, Diana; Muralidaran, Yuvashree; Romanholo Ferreira, Luiz Fernando; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Mulla, Sikandar I.; Mishra, Prabhakar (Springer Nature, 2025)
The widespread application of plastics and its eventual degradation to micro-sized or nano-sized plastics has led to several environmental concerns. Moreover, nanoplastics can easily cascade through the food chain accumulating in the aquatic organisms. Thus, our study focussed on investigating the hazardous impact of nano-sized plastics on aquatic species including Nitrobacter vulgaris, Scenedesmus sp, and Daphnia magna. Various concentrations of polystyrene nanoplastics ranging from 0.01 mg/L to 100 mg/L were tested against Nitrobacter vulgaris, Scenedesmus sp, and Daphnia magna. The minimum inhibitory concentration of polystyrene nanoplastics in Nitrobacter vulgaris was found to be 25 mg/L, and in Daphnia magna, the median lethal concentration 50 was observed to be 64.02 mg/L. Exposure of Scenedesmus sp with increasing nanoplastic concentrations showed a significant decrease in total protein (p < 0.001), and chlorophyll content (p < 0.01), whereas the lipid peroxidation increased (p < 0.001) significantly. Similarly, Nitrobacter vulgaris and Daphnia magna showed a significant decrease in catalase activity (p < 0.001) and an increase in lipid peroxidation levels (p < 0.01). Concomitant with lipid peroxidation results, decreased superoxide dismutase levels (p < 0.01) and protein concentrations (p < 0.01) were observed in Daphnia magna. Besides, the increasing concentration of polystyrene nanoplastics displayed an elevated mortality rate in Scenedesmus sp (p < 0.001) and Nitrobacter vulgaris (p < 0.01). Further, scanning electron microscopy analysis substantiated the morphological alterations in Nitrobacter vulgaris and Scenedesmus sp on exposure to polystyrene nanoplastics.
Keywords: Aquatic Ecosystem; Cytotoxicity; Ecotoxicity; Oxidative Stress; Polystyrene Nanoplastics